2013
DOI: 10.2478/achi-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Studies on adsorption capacity of cationic dyes on several magnetic nanoparticles

Abstract: In this study the dyes used are Basic fuchsin and Methylene blue. The adsorption was studied in relation to the metal in the ferrite, time of exposure and dye concentration. The highest adsorbtion capacity was observed for MgFe 2 O 4 at a dye concentration of 0.06 mM, adsorption percent of 88% in 3 hours. Desorption was also studied by redispersion in ethanol. The main adsorption mechanism is thought to be through electrostatic interaction, mainly due to surfactant groups present on the nanoparticles. The nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 14 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…Water pollution due to industrial dye effluent is a very serious problem which undergoes chemical as well as biological changes, consume dissolved oxygen, and destroy aquatic life [1][2][3]. Dyes are used in various industries such as construction, textile, paper, plastics, leather, cosmetics, etc., for the purpose of coloring the related products.…”
Section: Introductionmentioning
confidence: 99%
“…Water pollution due to industrial dye effluent is a very serious problem which undergoes chemical as well as biological changes, consume dissolved oxygen, and destroy aquatic life [1][2][3]. Dyes are used in various industries such as construction, textile, paper, plastics, leather, cosmetics, etc., for the purpose of coloring the related products.…”
Section: Introductionmentioning
confidence: 99%
“…However, this procedure is time consuming and requires multiple repetitions of the analysis of the biological samples in MS and MS/MS mode as well as in different ionization modes (positive and negative). Therefore in currently reported metabolomics studies the more advanced data acquisition techniques such as fast/rapid polarity switching (FPS) or auto MS/MS mode are sometimes used [4,8,9]. In the case of FPS technique MS spectra are recorded in both polarizations at the same time, however MS/MS analysis should be finally performed separately.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these drawbacks in this study, adsorbent materials ferrite nanoparticles M II Fe 2 O 4 (M II = Mg, Cu) were used in the removal process of dye from waste waters resulting from inkjet cartridges manufacturing. It was reported that these nanoparticles presented good efficiency as reusable adsorbents due to their reduced obtaining cost, high surface area and easy recovery using their magnetic properties [9,[16][17][18][19][20]. The ferrites nanoparticles studied in this paper were obtained by thermal decomposition of coordination compounds at lower temperatures and, its superiority in comparison with other oxalate precursor methods of the mixed oxides [21].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the easy of operation most of the researchers focused on the adsorption processes [6,7,9,15]. Anyway, this method presents some drawbacks such as: high cost, difficult disposal and regeneration [1,9]. In order to overcome these drawbacks in this study, adsorbent materials ferrite nanoparticles M II Fe 2 O 4 (M II = Mg, Cu) were used in the removal process of dye from waste waters resulting from inkjet cartridges manufacturing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation